Pediatric dumbbell-shaped orbital schwannoma with extension to the cranial cavity: A case report and literature review - Shao, Yongjia; Xi, Qian; Cheng, Ailan; Qian, Minghui; Chu, Shuguang (Frontiers in Neurology, 2023)
Orbital schwannomas are rare in children, especially those with intracranial extension. Herein, our report refers to a 12-year-old boy who had a cranial-orbital mass with a dumbbell-like appearance. The total neoplasms was successfully removed via a transcranial approach, and the pathological diagnostic result was schwannoma. Neither radiotherapy nor chemotherapy was performed after surgery, and no recurrences were observed for 3 months. Our report suggests that orbital schwannomas should be differentiated from other types of orbital tumors with sufficient evidence and that complete surgical resection remains the first choice to cure this disease.